2017
DOI: 10.1051/epjconf/201614501003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating cosmic rays and air shower physics with IceCube/IceTop

Abstract: Abstract. IceCube is a cubic-kilometer detector in the deep ice at South Pole. Its square-kilometer surface array, IceTop, is located at 2800 m altitude. IceTop is large and dense enough to cover the cosmic-ray energy spectrum from PeV to EeV energies with a remarkably small systematic uncertainty, thanks to being close to the shower maximum. The experiment offers new insights into hadronic physics of air showers by observing three components: the electromagnetic signal at the surface, GeV muons in the periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…This is in line with earlier results of the HiRes/MIA experiment [7] obtained for E 10 17 eV. While preliminary IceTop results [8] for GeV muons and 10 15 eV E 10 17 eV suggested that no excess is seen, they have been superseded by newer preliminary results [9] demonstrating the rise of the muon excess near 10 17 eV, consistent with the excess seen by HiRes/MIA (see also discussion in Ref. [10]).…”
Section: Introductionsupporting
confidence: 90%
“…This is in line with earlier results of the HiRes/MIA experiment [7] obtained for E 10 17 eV. While preliminary IceTop results [8] for GeV muons and 10 15 eV E 10 17 eV suggested that no excess is seen, they have been superseded by newer preliminary results [9] demonstrating the rise of the muon excess near 10 17 eV, consistent with the excess seen by HiRes/MIA (see also discussion in Ref. [10]).…”
Section: Introductionsupporting
confidence: 90%
“…The most recent SIBYLL model including this effect finds indeed a significant enhancement in the number of muons produced in the shower [101]. Note that since the suppression of the electromagnetic component by an enhanced ρ 0 production is a cumulative effect, depending on the number of generations of hadronic interactions that happen before the charged pions decay, the muon excess is expected to be reduced for lower energy primaries, and indeed no indications of a significant muon excess have been reported at energies below 0.1 EeV (although there is always an interplay between the expected number of muons and the inferred CR composition) [102,103].…”
Section: Proton Cross Section and Air Shower Muon Contentmentioning
confidence: 99%
“…15. There is definitely complementary information from neutrino telescopes to be added to the efforts in understanding hadronic interactions using air shower arrays and heavy-ion and hadronic accelerator experiments [104,105].…”
Section: Probe Of Cosmic Ray Interactions With Icecubementioning
confidence: 99%